Capability representation model for heterogeneous remote sensing sensors: Case study on soil moisture monitoring. (August 2015) - Fan, Hong; Li, Jia; Chen, NengCheng; Hu, Chuli
Abstract: Sensor capability information can be used as a basis for the integrated management of vast and heterogeneous remote sensing sensors in Global Earth Observation System of Systems environment. However, the existing representation of this information shows an inconsistent pattern, incomplete capability aspects, and casual expression forms, resulting in information silos among different systems. A sensor capability representation model (SCRM) is proposed in this study. Based on the Meta Object Facility architecture, a five-tuple hierarchical SCRM framework is formulated. Five specific representation element collections for typical remote sensing sensor types are developed to satisfy the requirements of detailed capability expression. The Open Geospatial Consortium Sensor Model Language is used as the expression form of the proposed SCRM. A prototype system is developed and a case study is conducted for a soil moisture monitoring application in Baoxie Town. The SCRM can also be extensively utilised for other environmental monitoring and modelling situations. Highlights: We propose a heterogeneous remote sensing sensor capability meta-model. We define a five-tuple sensor capability representation structure. We design an extension mode to support five typical types of RS sensors. A prototype system is designed and implemented. The model is applied in the multi-sensor monitoring of soil moisture.